Unmixing hyperspectral intimate mixtures - Nascimento, Jose (2014)
Proceedings of International Conference Conference Volume 7830 Image and Signal Processing for Remote Sensing XVI Lorenzo Bruzzone Toulouse, France | September 20, 2010